Transforming business with program management : integrating strategy, people, process, technology, structure, and measurement - Subramanian, Satish P. (Boca Raton, Florida : CRC Press, 2015)
This book illustrates a tested program management roadmap along with the supporting comprehensive frameworks to successfully execute business transformation programs, formulated strategies, and strategic initiatives. It outlines the steps to successfully transform any business and deliver tangible business outcomes. The author details the processes, techniques, and tools that a program management team can customize and easily implement on any type of strategic initiative within the private or public sector environment to deliver and sustain the expected business outcomes and benefits. It showcases program management best practices and lessons learned though real-world case studies spanning different industry sectors and functional domains. -- Edited summary from book.
Chapter 1. Executive overview -- chapter 2. Success starts upfront : describe the problem accurately -- chapter 3. Articulate the program vision and objectives -- chapter 4. Secure cross functional executive sponsorship -- chapter 5. Development and implement a governance model -- chapter 6. Define success, outcomes, and key values indicators -- chapter 7. Invest in planning and creating an integrated approach -- chapter 8. Drive strong partnership and stakeholder engagement -- chapter 9. Provide leadership across all levels -- chapter 10. Monitor aggressively and have contingencies -- chapter 11. Create and implement on operations transition plan -- chapter 12. Executive summary.
Includes bibliographical references and index.
Keywords: PROJECT MANAGEMENT